A new corrective technique for adolescent idiopathic scoliosis: convex manipulation using 6.35 mm diameter pure titanium rod followed by concave fixation using 6.35 mm diameter titanium alloy - Terai, Hidetomi (Scoliosis, 2015)
BACKGROUND: It has been thought that corrective posterior surgery for adolescent idiopathic scoliosis (AIS) should be started on the concave side because initial convex manipulation would increase the risk of vertebral malrotation, worsening the rib hump. With the many new materials, implants, and manipulation techniques (e.g., direct vertebral rotation) now available, we hypothesized that manipulating the convex side first is no longer taboo. METHODS: Our technique has two major facets. (1) Curve correction is started from the convex side with a derotation maneuver and in situ bending followed by concave rod application. (2) A 6.35 mm diameter pure titanium rod is used on the convex side and a 6.35 mm diameter titanium alloy rod on the concave side. Altogether, 52 patients were divided into two groups. Group N included 40 patients (3 male, 37 female; average age 15.9 years) of Lenke type 1 (23 patients), type 2 (2), type 3 (3), type 5 (10), type 6 (2). They were treated with a new technique using 6.35 mm diameter different-stiffness titanium rods. Group C included 12 patients (all female, average age 18.8 years) of Lenke type 1 (6 patients), type 2 (3), type 3 (1), type 5 (1), type 6 (1). They were treated with conventional methods using 5.5 mm diameter titanium alloy rods. Radiographic parameters (Cobb angle/thoracic kyphosis/correction rates) and perioperative data were retrospectively collected and analyzed. RESULTS: Preoperative main Cobb angles (groups N/C) were 56.8°/60.0°, which had improved to 15.2°/17.1° at the latest follow-up. Thoracic kyphosis increased from 16.8° to 21.3° in group N and from 16.0° to 23.4° in group C. Correction rates were 73.2% in group N and 71.7% in group C. There were no significant differences for either parameter. Mean operating time, however, was significantly shorter in group N (364 min) than in group C (456 min). CONCLUSION: We developed a new corrective surgical technique for AIS using a 6.35 mm diameter pure titanium rod initially on the convex side. Correction rates in the coronal, sagittal, and axial planes were the same as those achieved with conventional methods, but the operation time was significantly shorter.